1987
DOI: 10.1007/bf00269458
|View full text |Cite
|
Sign up to set email alerts
|

Thalamo-cortical connections and their correlation with receptive field properties in the cat's lateral suprasylvian visual cortex

Abstract: Areas PMLS and PLLS of the cat's lateral suprasylvian visual cortex display an interesting global organization of local features in their single unit response properties: direction preference is centrifugally organized and velocity preference increases with eccentricity. In addition it has previously been shown that binocular interactions are strongest around the visual field center. This characterizes the LS areas as apt for the analysis of optic flow fields and for visual processing in various kinds of visuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Thus, extrastriate synaptic input may also be important in shaping RF properties in the LPl. Our group (Piché et al 2013) has described the first-order RF spatial profile of neurons in the lateral suprasylvian (LS) cortex, which is reciprocally connected with the LPl (Berson and Graybiel 1983;Rauschecker et al 1987). We found that LS neurons have larger dark subfields and displayed RF spatial organization types highly similar to those found in the LPl, with comparable occurrence rates (Piché et al 2013).…”
Section: Discussionmentioning
confidence: 69%
“…Thus, extrastriate synaptic input may also be important in shaping RF properties in the LPl. Our group (Piché et al 2013) has described the first-order RF spatial profile of neurons in the lateral suprasylvian (LS) cortex, which is reciprocally connected with the LPl (Berson and Graybiel 1983;Rauschecker et al 1987). We found that LS neurons have larger dark subfields and displayed RF spatial organization types highly similar to those found in the LPl, with comparable occurrence rates (Piché et al 2013).…”
Section: Discussionmentioning
confidence: 69%
“…Lesion studies show that directional selectivity depends on input from areas 17, 18 and 19, both in the superficial laminae of the superior colliculus (Stein, 1988) and in the PMLS . Measurements of response latencies and laminar analysis of PMLS cells with regard to axial direction preference support the conclusion that the centrifugal direction bias is generated intracortically (Rauschecker et al 1987b). However, PMLS directional selectivity recovers after early occipital lesions , implying that although this input does usually determine directional 656 CENTRIETC TGA L PREFERENC'E IN KITTEN PAILS selectivity, it is not indispensable.…”
Section: Discussionmentioning
confidence: 70%
“…In order to differentiate between the motion of the visual surrounding versus self-motion, the central nervous system must integrate multimodal signals including visual and vestibular signals in order to extract the origin and direction of the perceived movement. As mentioned above, cortical visual and vestibular interaction has been first suggested in the visual lateral suprasylvian cortex in cat (Vanni-Mercier and Magnin, 1982a,b; Ventre, 1985a,b; Rauschecker et al, 1987; Tusa et al, 1989) and in the middle temporal sulcus in macaque monkey (Dursteler and Wurtz, 1988; Komatsu and Wurtz, 1988a,b). These visual temporal cortical areas called MT (middle temporal) and MST (middle superior temporal) have a critical role in visual motion processes linked to smooth pursuit, heading perception and optokinetic-related information, all involving velocity signals triggered during ego-motion in monkey.…”
Section: Is the Temporal Cortex Involved In A Velocity Pathway?mentioning
confidence: 87%